Pernikahan Baru Tanpa Akta Cerai - Rosdalina Bukido; Christofer Visal Solang; Ridwan Jamal; Misbahul Munir Makka; Faradila Hasan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2019)
This study explains that Paradigms are a concept of thought that is acquired in certain problems or cases so that the delivery can be understood and understood, the problem being examined is the main factor of divorce what happened to the community, not through the judiciary and the role of Islamic religious instructors in responding to the new marriage process in the community of the Buku Raya village in the Belang District that did not have proof of divorce. The researcher approached qualitative research (case study) in order to obtain data in the field validly and aimed to describe and analyze critically what happened in the field so as to produce data that the role of Islamic religious instructors in providing understanding to society must be truly understood by the community itself so that they are not easy to make decisions, and religious educators are also present from people who have good religious understanding. This research is expected to be able to provide advice and thoughts to the Community and the Government specifically the Ministry of Religion in selecting and sorting extension workers in the religious affairs office.